Testing The Effectiveness of Using a Board Game on English Vocabulary in Biology Learning for Review and Evaluation to Improve Student Performance - Umi Hani; Anik Ghufron (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study investigates the effectiveness of an IGCSE Biology board game as an alternative learning tool to address limited digital access, enhance students’ understanding of English biological vocabulary, encourage social interaction, and improve learning performance. Using a quantitative approach with a true experimental pretest posttest control group design, the research involved 80 eighth-grade students at Aichurok Bishkek High School, Kyrgyzstan. Sixty students participated in the experimental group, while 20 students formed the control group. The study was conducted between April and May 2025. Data were analyzed using Microsoft Excel and SPSS, applying statistical tests such as normality, homogeneity, Wilcoxon Signed Rank, Mann Whitney U, correlation, and reliability analyses. The results demonstrate that the board game significantly enhanced students’ vocabulary mastery, engagement, communication, and conceptual understanding. A statistically significant difference was found between the post-test scores of the experimental and control groups (Asymp. Sig. = 0.000). Reliability analysis showed excellent consistency for the board game instrument and student engagement, while collaboration and communication indicators were moderately reliable. Teacher observations also revealed continuous improvement across instructional cycles. Overall, the findings indicate that the IGCSE Biology board game is an effective and engaging learning medium that supports academic achievement and the development of 21st-century skills. Further studies with larger samples and longer implementation periods are suggested to explore its long-term effectiveness.